Breast Implants on Computed Tomography—A Pictorial Review of Normal and Pathologic Findings - Gossner, Johannes (Indian Journal of Radiology and Imaging, 2021)
Breast augmentation with implants is frequently performed. Therefore breast implants can be seen quite frequently on computed tomography (CT) of the body. This offers the possibility to detect incidental pathology and help to improve patient outcome. Basic knowledge about imaging findings of breast implants on CT is therefore needed for radiologists reporting body CT. CT may also be used for further workup of breast implants if magnetic resonance imaging (MRI) is contraindicated or not available. The purpose of this pictorial review is to give a brief overview of normal and pathologic findings of breast implants on CT.
Keywords: breast implant; computed tomography; pathology; capsular contracture; capsular rupture